Penilaian Kesesuaian Ecotourism di Pulau Gili Genting menggunakan Analisis Daerah Operasi Objek Dan Daya Tarik Wisata Alam (ADODTWA) - Dyah Rina; Rahmad Fajar Mauliddy; Nailul Insani (SPATIAL: Wahana Komunikasi dan Informasi Geografi, 2021)
Travel & Tourism Competitiveness Index of Indonesia was scored up to 4.3 with 2.8% improvement from 2017, and reaching 11.0% above the global average score. Unfortunately, Indonesia is poorly rated for Environmental Sustainability aspect at 135th place. In addition, nature-based tourism which’s relative suitable with Indonesia's regional character, is kind of tourism system that prioritizes the tourist’s experience due directly enjoying a natural phenomenon and is one of tourism system that’s rapidly increase recently. This research gol was to assess and evaluating the suitability aspects and potential of natural tourism in the Gili Genting Island, using the Evaluation of the Operational Area Analysis of Natural Tourism Objects and Attractions Instrumen (ADO-ODTWA in Indonesia) with indicators by Director General of PHKA. The results of this evaluation, shown that Gili Genting Island obtained an average value of 591.6 and including in the second class which indicate that "this area is Moderate Potential for Tourism Development”. This result show that tourism potential in this area was quite feasible to develop. The development potential is supported due the high value of tourist attraction which shows the high potential of natural tourism. In addition, the social local community which is relatively thick with the culture of mutual cooperation typical of the local Madurese also can be another unique attraction for tourism development due Ecotourism system in the future.